Product and Service Innovation in MSMEs for Competitive Advantage against Low Cost Imports - Muchammad Firman Mauludin; Pesta Asni W Napitupulu; Eny Yuniyati (Jobmark: Journal of Branding and Marketing Communication, 2022)
The influx of low-cost imported products into Indonesia has intensified competition for Micro, Small, and Medium Enterprises, particularly in urban markets such as Surabaya, where price efficiency and mass production dominate. This study examines how MSMEs develop product and service innovation as adaptive strategies to respond to import competition and build sustainable competitive advantage. Using an interpretive qualitative case study approach, data were collected through in-depth interviews, field observations, and documentation, and analyzed using the interactive model of data reduction, thematic analysis, and conclusion drawing. The findings reveal that MSMEs perceive imported products as structural competitive pressure that reshapes market dynamics. In response, they pursue product innovation through local differentiation, redesign packaging as a strategic communication tool, enhance service innovation through customer experience, adopt digital marketing via e-commerce platforms, and leverage cultural narratives as branding assets. In addition, the growth of culinary tourism in Surabaya creates new competitive spaces that require the integration of innovation with local identity. Theoretically, this study reinforces differentiation as a key competitive strategy. It extends the Resource-Based View by highlighting intangible assets such as creativity, social capital, and cultural identity as critical resources. Practically, it underscores the importance of innovation-driven strategies and digital capability development to strengthen MSME competitiveness in the context of global trade pressures